POLA USAHA PETERNAKAN AYAM RAS PEDAGING DI ACEH - Jamilah Jamilah (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2016)
The study aims to analyze the pattern of broiler breeding business in Aceh. Identify the pattern of farm is a descriptive qualitative based businesses on aspects of livestock production to marketing of livestock products, also includes opportunities, constraints, and the development of farming businesses in North Aceh District.The results showed that businesses broiler farms in North Aceh Regency developing three (3) business pattern is the effort broiler farms with their own capital by farmers, businesses broiler farms built Department of Animal Husbandry and Animal Health, and businesses broiler farms with a partnership inti-plasma between the companies as the core and farmers as plasma. The main problem faced is the breeder is unable to handle the high feed costs and the risk of death of chickens while chicken prices fluctuate. On the other hand, the lack of guidance and supervision as well as the moral hazard caused the government-owned farming businesses are not able to develop properly. In this condition, the farm-system partnerships are more profitable than other business patterns